Education, Training, LLL and Youth Employability in Europe, today: trends, political priorities, benchmarks, challenges and the state of play - Papadakis, Nikos (Education Sciences, 2020)
The paper focuses on the ongoing European Education &Training Strategy, in the context of the “Europe2020”, underlining the main modifications in education, training and LLL (indicators, benchmarks, new policy tools developed and implemented etc). It provides a brief presentation of the major priorities of the E&T 2020 Work Programme, highlighting the emphasis on reskilling, LLL, competence - based learning and VET as prime movers for increasing employability and promoting social inclusion. Then, the paper proceeds in an critical review of the current state of play regarding EU M-S performance in benchmarks such as low achievers in the key-competences, early school leaving, early childhood education and care, tertiary educational attainment, adult participation in learning, recent graduates’ employability, while it raises issues related to education poverty and socio- economic and educational inequalities.